"Rigor for What?" Social Studies Teacher Conceptions and Enactments of Instructional Rigor. Issue 5 (3rd September 2017) - Gibbs, Brian
ABSTRACT: Taken from a larger qualitative study, this article argues that rather than an encompassing uniform definition, rigor, as understood and enacted by social studies teachers, exists on a complicated spectrum. Teacher placement on this spectrum was influenced by teacher life experience, teacher interpretation of student need, pedagogy employed, how content should be used, and the role of the teacher in the lives of students. How rigor is conceived and enacted by social studies teachers can have a profound impact on the types of citizens schools nurture and develop and the role school can play in the lives of students.